Effect of turmeric powder (Curcuma longa L.) and ascorbic acid on physical characteristics and oxidative status of fresh and stored rabbit burgers. (December 2015) - Mancini, Simone; Preziuso, Giovanna; Dal Bosco, Alessandro; Roscini, Valentina; Szendrő, Zsolt; Fratini, Filippo; Paci, Gisella
Abstract: The objective of this study was to evaluate the effect of Curcuma longa powder and ascorbic acid on some quality traits of rabbit burgers. The burgers (burgers control with no additives; burgers with 3.5 g of turmeric powder/100 g meat; burgers with 0.1 g of ascorbic acid/100 g meat) were analyzed at Days 0 and 7 for pH, color, drip loss, cooking loss, fatty acid profile, TBARS, antioxidant capacity (ABTS, DPPH and FRAP) and microbial growth. The addition of turmeric powder modified the meat color, produced an antioxidant capacity similar to ascorbic acid and determined a lower cooking loss than other formulations. Turmeric powder might be considered as a useful natural antioxidant, increasing the quality and extending the shelf life of rabbit burgers. Highlights: Addition of 3.5% of Turmeric powder or 0.1% ascorbic acid in rabbit burger was assessed. The addition of turmeric powder produced an antioxidant capacity similar to ascorbic acid. Addition of Turmeric powder modified burger color parameters.